2019
DOI: 10.3390/ijerph16193753
|View full text |Cite
|
Sign up to set email alerts
|

Contamination by Antibiotic-Resistant Bacteria in Selected Environments in Thailand

Abstract: This study determined the presence of important antibiotic-resistant bacteria in selected environments in Thailand, including wastewater samples from 60 hospitals; washed fluid, leachate, flies, cockroaches, and rats collected from five open markets; washed fluid from garbage trucks; and stabilized leachate from a landfill facility. At least one type of antibiotic-resistant bacteria was isolated from all samples of influent fluid before treatment in hospitals, from wastewater treatment tank content in hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We identified estimates ( Table 1 ) for the prevalence of gut colonisation with ESBL-producing E. coli in Thailand for healthy humans across an eight-year timeframe (2004–2012) [ [22] , [23] , [24] , 28 , 29 ], estimates of sample level positivity for resistant bacteria in rectal swabs from animals and fresh food from Thailand in 2012–2013 [ 24 ], and environmental estimates of the proportion of bacteria that are resistant in Thailand from canal water sources [ 24 ], stagnant water on food animal farms, and liquid from hospital wastewater treatment tanks [ 30 ]. These data were used to calculate lower and upper bounds (95% credible intervals) in order to calibrate our model to a national-level Thailand-specific setting.…”
Section: Methodsmentioning
confidence: 99%
“…We identified estimates ( Table 1 ) for the prevalence of gut colonisation with ESBL-producing E. coli in Thailand for healthy humans across an eight-year timeframe (2004–2012) [ [22] , [23] , [24] , 28 , 29 ], estimates of sample level positivity for resistant bacteria in rectal swabs from animals and fresh food from Thailand in 2012–2013 [ 24 ], and environmental estimates of the proportion of bacteria that are resistant in Thailand from canal water sources [ 24 ], stagnant water on food animal farms, and liquid from hospital wastewater treatment tanks [ 30 ]. These data were used to calculate lower and upper bounds (95% credible intervals) in order to calibrate our model to a national-level Thailand-specific setting.…”
Section: Methodsmentioning
confidence: 99%
“…The high prevalence of ESBL-Ec in wastewater discharged from the urban food markets, with more than 95% of samples positive, and a high mean concentration of ESBL-Ec (5.59 log 10 CFU/100 ml) is notable. Of even greater concern is the high prevalence (30%) of CR-Ec in wastewater samples with a mean concentration of 3.48 log 10 CFU/100 ml which is higher than the concentrations of CR-Ec in community wastewater reported by other studies in Bangladesh and Thailand (Islam et al, 2017;Thamlikitkul et al, 2019). Previous studies reported that hospital waste is a major source of CR-Ec in the environment, especially where hospital waste is disposed directly to the environment without treatment (King et al, 2020;Lamba et al, 2017;Al Salah et al, 2020;Daoud et al, 2018;Park et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The copyright holder for this preprint this version posted June 11, 2020. ; https://doi.org/10.1101/2020.06.09.20126433 doi: medRxiv preprint We identified estimates (Table 1) for the prevalence of gut colonisation with ESBLproducing E. coli in Thailand for healthy humans across an eight-year timeframe (2004 -2012) [22][23][24]28,29], estimates of sample level positivity for resistant bacteria in rectal swabs from animals and fresh food from Thailand in 2012-2013 [24], and environmental estimates of the proportion of bacteria that are resistant in Thailand from canal water sources [24], stagnant water on food animal farms, and liquid from hospital wastewater treatment tanks [30]. These data were used to calculate lower and upper bounds (95% credible intervals) in order to calibrate our model to a nationallevel Thailand-specific setting.…”
Section: Methodsmentioning
confidence: 99%